Medan City Management in Increasing Economic Competitiveness in the Digital Era - Lubis, Hasrita; Nasti, Nilawati; Amirulsyah, Amirulsyah; Syarkawi, Ahmad (Medan Resource Center, 2024)
The city of Medan, as one of the important economic centers in North Sumatra, faces challenges in increasing its economic competitiveness in the digital era. This study explores how Medan City management can utilize digitalization to strengthen economic competitiveness through implemented digitalization policies and strategies. Qualitative research methods with case studies were used to collect data from in-depth interviews, observations, document studies, and focus group discussions. The results of the study show that digitalization policies, including investments in digital infrastructure and technology training, have had a positive impact on MSMEs and attract investment. However, there are significant challenges such as the digital divide between city centers and suburbs as well as cybersecurity concerns. This research recommends improving infrastructure, strengthening the cybersecurity system, as well as more intensive training and support for MSMEs and the creative economy sector. By implementing this recommendation, the City of Medan can optimize the benefits of digitalization and increase its economic competitiveness in a sustainable manner in the digital era.